2018
DOI: 10.1167/iovs.18-24475
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vascular Reactivity in Central Serous Chorioretinopathy

Abstract: Unlike healthy subjects, retinal blood flow in patients with CSCR seems affected by rapid increases in BP and OPP. Our study suggests that the autoregulatory mechanisms controlling retinal microcirculation are not entirely able to counteract overperfusion in patients with CSCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…This study also showed that under exertion, patients with CSC have significantly increased blood flow compared to that of healthy subjects (Cardillo Piccolino et al. 2018). Another study of the retinal vessels in patients with CSC using dynamic vessel analysis showed a reduced dilation of the venous vessels to a flicker stimulus, the authors speculated that increased sympathetic tone may be responsible for this (Tomasso et al.…”
Section: Introductionmentioning
confidence: 65%
“…This study also showed that under exertion, patients with CSC have significantly increased blood flow compared to that of healthy subjects (Cardillo Piccolino et al. 2018). Another study of the retinal vessels in patients with CSC using dynamic vessel analysis showed a reduced dilation of the venous vessels to a flicker stimulus, the authors speculated that increased sympathetic tone may be responsible for this (Tomasso et al.…”
Section: Introductionmentioning
confidence: 65%
“…There are many methods available to elicit a dynamic response in the retinal microvasculature. The handgrip test and hyperoxic conditions have been previously used to induce retinal vasoconstriction ( 27 , 30 , 51 , 52 ), while the flicker test and hypoxia have been reported to illicit a vasodilatory response ( 27 , 30 , 53 ). Currently, these techniques are limited to research use, however they may have clinical applicability with standardization of methods and reporting of test findings.…”
Section: Discussionmentioning
confidence: 99%
“…The hypoxia challenge test is standardized by the British Thoracic Society to assess whether individuals with stable respiratory disease are suitable for a long-haul flight by exposing them to reduced oxygen levels similar to those encountered in an airplane cabin ( 54 ). The handgrip test is used to assess cardiovascular autonomic function ( 42 ), and has been used for a wide variety of clinical indications ( 33 , 51 , 52 ). Despite their convenience, both tests have their limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using OCTA reported contrasting results on the change of DCP density in CSC. Piccolino et al showed that DCP density was lower in CSC patients compared with healthy controls 14 , while Nelis et al showed that CSC patients had higher DCP density and larger FAZ area than did healthy controls 9 . In our study, CSC patients had a lower FCP density, smaller FAZ area, and higher DCP density than did healthy controls, albeit without statistical significance (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, visual impairments may persist in some patients even after the dissipation of fluid, due to disruption of the retinal microarchitecture, subretinal fibrosis, and scarring or atrophy of the RPE 8 10 . There is still controversy among several studies using coherence tomography angiography (OCTA) whether the macular vascular alteration occurs at the early stage of CSC 9 , 11 14 . Thus, more sensitive and accurate imaging modalities are required for the early detection of changes in retinal blood flow.…”
Section: Introductionmentioning
confidence: 99%